2021
DOI: 10.21203/rs.3.rs-446795/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fabrication and Characterization of an Antibacterial Chitosan/Silk Fibroin Electrospun Nanofiber Loaded with a Cationic Peptide for Wound-dressing Application

Abstract: Wound infections are still problematic in many cases and demand new alternatives for current treatment strategies. In recent years, biomaterials-based wound dressings have received much attention due to their potentials and many studies have been performed based on them. Accordingly, in this study, we fabricated and optimized an antibacterial chitosan/silk fibroin (CS/SF) electrospun nanofiber bilayer containing different concentrations of a cationic antimicrobial peptide (AMP) for wound dressing applications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Our results showed that this scaffold, in addition to having antimicrobial properties, facilitates the proliferation of fibroblasts and increases cell and cell adhesion. It also indicated suitable mechanical attributes, high water uptake, appropriate biodegradation rate, and a controllable release (Khosravimelal et al 2021). In comparison with this study, the current sponge had a stunning antibacterial effect at a concentration of 16 µg/ml, which could be related to the mentioned properties of the sponge Scaffolds.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our results showed that this scaffold, in addition to having antimicrobial properties, facilitates the proliferation of fibroblasts and increases cell and cell adhesion. It also indicated suitable mechanical attributes, high water uptake, appropriate biodegradation rate, and a controllable release (Khosravimelal et al 2021). In comparison with this study, the current sponge had a stunning antibacterial effect at a concentration of 16 µg/ml, which could be related to the mentioned properties of the sponge Scaffolds.…”
Section: Discussionsupporting
confidence: 51%
“…CM11, as a short cationic peptide derived from cecropin and melittin peptides, is comprised of 11 amino acid residues (WKLFKKILKVL-NH 2 ) that have been shown to have a broad-spectrum antibacterial activity against gram-negative and positive bacteria. Based on studies, AMPs such as CM11 peptide can be added to biomaterial wound dressings to improve their antiinfective properties (Moghaddam et al 2012, Amani et al 2015, Khosravimelal et al 2021). Accordingly, a potential antibacterial wound dressing of sponge SF/Gel scaffolds comprising various concentrations of CM11 peptide has been investigated.…”
Section: Introductionmentioning
confidence: 99%